2000
DOI: 10.1093/mutage/15.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and characterization of micronuclei induced by the antitumour agent ASE [3beta-hydroxy-13alpha-amino-13,17-seco-5alpha-androstan-17-oic-13,17-lactam-p-bis(2-chloroethyl)amino phenylacetate] in human lymphocyte cultures

Abstract: increased lifespan over controls in the treatment of L1210 N.A.Demopoulos leukemia in mice and a 150% increased lifespan in the treatment of P388 leukemia (Wampler and Catsoulacos, 1977).Division of Genetics, Cell and Developmental Biology, Department of Moreover, ASE has given good activity against B 16 melanoma Biology, University of Patras, 26500 Patras, Greece in C 57 b 1 mice and T 8 Guerrin tumors in rats (Catsoulacos and 3β-Hydroxy-13α-amino-13,17-seco-5α-androstan-17- Wampler, 1982). In addition, ASE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…However, it has been noted previously that there are very few genotoxic agents that induce only C þ MN or only C À MN [Schuler et al, 1997]. Indeed, many clastogens [Vlachodimitropoulos et al, 1997;Andrianopoulos et al, 2000;Kouloumenta et al, 2005] and aneugens [Bakou et al, 2002] produce both types of MN. Myhr et al [1990] reported that …”
Section: Discussionmentioning
confidence: 98%
“…However, it has been noted previously that there are very few genotoxic agents that induce only C þ MN or only C À MN [Schuler et al, 1997]. Indeed, many clastogens [Vlachodimitropoulos et al, 1997;Andrianopoulos et al, 2000;Kouloumenta et al, 2005] and aneugens [Bakou et al, 2002] produce both types of MN. Myhr et al [1990] reported that …”
Section: Discussionmentioning
confidence: 98%
“…MN caused by breakage events were noticed in human lymphocytes treated with antineoplastic drug ASE (Andrianopoulos et al, 2000). Teniposide, an anti-tumor drug used for treatment of childhood acute lymphocytic leukemia, induced MN with a peak frequency at 16 h after treatment, which was correlated with cell survival decline (Adiga and Jagetia, 1999).…”
Section: Micronuclei and Genotoxic Agentsmentioning
confidence: 99%
“…It was reported that melphalan, in addition to its clastogenicity, increased micronuclei (MN) originating from chromosome delay events in MCL-5 and h1A1v2 cells (Phousongphouang et al, 2000). Although ASE, a homo-aza-steroidal ester of PHE [p-N,N-bis(2-chloroethyl) aminophenylacetic acid], induced MN that primarily formed owing to chromosome breakage, a weak aneugenic potential was reported in human lymphocyte cultures in vitro (Andrianopoulos et al, 2000). Kouloumenta et al (2005) showed that two steroidal analogs of PHE exerted dual genetic activity, clastogenic and aneugenic.…”
Section: Introductionmentioning
confidence: 99%